INVESTIGATING THE PROTECTIVE EFFECTIVENESS OF THE SHIELDING PARAMETERS FOR DIAGNOSTIC X-RAY ROOMS IN SOME SELECTED HOSPITALS IN AGBOR METROPOLIS - DELTA STATE (FUDMA JOURNAL OF SCIENCES, 2022)
Over exposure to x-rays is capable of producing serious health hazards and capable of causing death due to its ionizing nature. In the determination of effective primary and secondary shielding parameters of some hospitals in Agbor, a radiation detector, Geiger Muller Counter 320 plus was used for the measurement of radiation in the selected x-ray centers chosen in other to ascertain the degree of exposure of x-ray machines at exactly 1m from the primary source. The work was carried out for a period of 12 weeks in each of the selected hospitals simultaneously. A total of 145 patients were examined in central hospital Agbor, 110 in central hospital Abavo and 125 in Nkonye hospital Agbor. The patient’s examination records containing types of examination each day, peak tube voltage, tube current and exposure time including the actual number of films used were obtained. Results obtained from the three hospitals investigated were found to be inconformity with the recommendations of National Commission on Radiological and Protection (NCRP) (70) and (116) protocols. Protective shielding parameters’ results obtained in this study were lower than the standard recommended maximum values. The study showed that the walls of the x-ray rooms of these hospitals investigated have adequate shielding parameters and as such may not require any additional primary structural shielding barriers. It is therefore concluded that the X-ray shielding facilities for diagnostic x-ray rooms in the selected hospitals in Agbor metropolis were adequate and safe radiologically for patients and staff respectively.
Keywords: X-ray, shielding, patients, exposure, parameters, radiologically.